2009
DOI: 10.1007/s12187-009-9050-x
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Adolescent Life Satisfaction and Parenting

Abstract: This study examined longitudinal relationships between adolescent life satisfaction (LS) and perceived parental support, parental behavioral control, and parental autonomy granting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 49 publications
(75 reference statements)
3
31
0
5
Order By: Relevance
“…All items are shown in Table 1. The Cronbach's alpha coefficients of internal consistency were found between .83 and .88 in former studies (e.g., Gilman and Huebner 2006;Ng et al 2015;Saha et al 2010). Test-retest reliability coefficients have been reported as .74-.76 based on a 1-2 week time interval and .64, .53, and .51 across 1-month, 1-year, and 2-year intervals, respectively (Huebner 1991a;Huebner et al 2005).…”
Section: Measurementioning
confidence: 94%
See 1 more Smart Citation
“…All items are shown in Table 1. The Cronbach's alpha coefficients of internal consistency were found between .83 and .88 in former studies (e.g., Gilman and Huebner 2006;Ng et al 2015;Saha et al 2010). Test-retest reliability coefficients have been reported as .74-.76 based on a 1-2 week time interval and .64, .53, and .51 across 1-month, 1-year, and 2-year intervals, respectively (Huebner 1991a;Huebner et al 2005).…”
Section: Measurementioning
confidence: 94%
“…Proctor et al (2009) reviewed the psychometric properties of the major LS measures appropriate for youth, concluding that the SLSS was the most well-validated measure. More specifically, evidence has consistently suggested that the SLSS is a reliable and moderately stable measure of global LS in American children and adolescents (e.g., Gilman and Huebner 2006;Saha et al 2010). Evidence also supported its criterion, convergent and discriminant validity (Dew and Huebner 1994;Huebner 1991a, b;Huebner and Alderman 1993;Seligson et al 2003).…”
mentioning
confidence: 95%
“…Health, health risk behaviours, long-term health conditions and mental health are all other important individual factors that have been confirmed to be influential in life satisfaction of young people by other studies (Fujita & Diener, 2005;Saha et al, 2010;Bayram et al, 2012;Jose & Hansen, 2012;Nesterko, et al, 2013;Chappel, o et al, 2014).…”
Section: Individual Factorsmentioning
confidence: 80%
“…It is obvious that this period can be a potentially challenging time for young people. The period of adolescence is considered by extreme mood and difficult behaviour changes (Saha,Huebner,Suldo,Valois, 2010). However, it is assumed that most young people growth through the years of adolescence period unaffectedly, a period that is designated as the period of "storm and stress" (Goldbeck, et al, 2007).…”
Section: Young People and Immigrationmentioning
confidence: 99%
See 1 more Smart Citation